KEPUASAN PELANGGAN TERHADAP PRODUK BISNIS INKUBATOR PROGRAM STUDI PKK KONSENTRASI TATA BUSANA - Sawitri, Sicilia; Rachmawati, Rina (Jurnal Penelitian Pendidikan, 2014)
Home Economics Incubator Bussiness was created as a result of a National Strategy research in 2013, created some products. The quality of the products will be known by asking to the costumer satisfaction. The aim of this research want to know how high the costumer satisfaction after used the products of Home Economic Incubator Business. By using survey method the research was conducted. The population and the samples of this research were all of the buyer who used the products. Data were collected by using Costumer Satisfaction Quetionary, and were analized by prosentase descriptive analyze. The result of this research shew that the costumersâ satisfaction were very high (82 %). The suggestions were submitted: (1) Needs design product development, (2) Needs coordination of all faculty members, such as: dean, the chief of Home Economics study programs, lecturers, and students, (3) Needs a new work to promote the products.